DIGITAL MARKETING UNTUK PEMBERDAYAAN MASYARAKAT BINAAN YAYASAN SOKOGURU UNGARAN - Ragil Saputra; Eko Adi Sarwoko; Dinar Mutiara KN; Rismiyati Rismiyati; Edy Suharto (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The Sokoguru Foundation is a non-governmental organization (NGO), with one of its activities which is a place for empowering the communities. After conducting an interview with the foundation managers and a survey of the member of the community, the results show that the ability to do entrepreneurship online is essential for the community. Therefore, the community services’ team provide training for the community about the use of social media, especially using Instagram to do digital marketing.This community service activity methodology uses a Participatory Rural Approach in the form of training and mentoring. The service is carried out in 3 stages: preparation, training and evaluation. Preparation is done by seeking information on material requirements for training. The training stage is carried out using an online system with Zoom Meeting (due to COVID-19 19 pandemic). Next, the training is filled with the presentation from the community service’s team, question and answer and sharing experiences.The result of the evaluation, this service activity adds new knowledge for participants (100%), usefulness (52.6%: very useful, 47.4%: useful). As well as increasing interest in online marketing by 73.7% from the previous 57%. Apart from scientific articles, the output of this activity is in the form of training modules, articles on the Kompas mass media, and video documentation on the YouTube channel.